Reading Fatwas of MUI a Perspective of Maslahah Concept - Maskur Rosyid; M. Nurul Irfan (Syariah: Jurnal Hukum dan Pemikiran, 2019)
Abstrak: Kemaslahatan dan kebaikan manusia merupakan tujuan pokok setiap bentuk peratuan, termasuk fatwa-fatwa Majelis Ulama Indonesia (MUI). Salah satubidang fatwa yang diterbitkan MUI adalahhukumkeluarga. Fokusutamatulisaniniadalahmembacaulang dan menganalisa fatwa-fatwa MUI dalambidanghukumkeluargadenganperspektifkonsepmaslahatmayoritas fuqaha yang juga telahditerbitkandalam Fatwa MUI tentangKriteriaMaslahatNomor: 6/MUNAS VII/MUI/10/2005. Fatwa-fatwa tersebut, dilihatmenggunakanparadigmakonsepmaslahat, adakalanya masuk dalam kategori maṣlaḥahmu‘tabarah, maṣlaḥahmursalah, dan adaindikasibeberapa fatwa yang masuk kedalam kategori maṣlaḥah mulghah. Adapun fatwa MUI dalam bidang hukum keluarga yang dimaksud dalam tulisan ini yaitu fatwa tentang Aborsi, tentang Perkawinan Beda Agama, tentang Kewarisan Beda Agama, tentang Perkawinan Di BawahTangan (sirri, tidak dicatatkan), dan tentang Nikah Wisata.Kata kunci: Maṣlaḥah, GradasiMaṣlaḥah, MUI, HukumKeluargaAbstract: Human benefit and goodness are the main objectives of every form of regulation, including the fatwas of the Council of Indonesian Ulama (MUI). One of the fatwa fields issued by MUI is family law. The main focus of this paper is to reread and analyze the fatwas of the MUI in the field of family law with the perspective of the concept of majority fuqaha masses which have also been published in the MUI Fatwa concerning the Maslahat No. 6 / MUNAS VII / MUI / 10/2005. These fatwas, are seen using the concept of maslahat, sometimes include to the category of maṣlaḥahmu‘tabarah, maṣlaḥahmursalah, and there are indications of several fatwas that include to the category of maṣlaḥahmulghah. The fatwas of the MUI in the field of family law referred to in this article is a fatwa on Abortion, concerning Differential Marriage, about Different Religions, About Marriage Under the Hand (sirri, not recorded), and about Tourism Marriage.Keywords: Maṣlaḥah, Gradation of Maṣlaḥah, MUI, Family Law